English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

ax + bx = a^2 + 2ab +b^2?

I can not understand this problem. My book does not even explain it well. Can someone please show me how to solve this. ^^

2007-01-12 15:52:27 · 8 answers · asked by Lizzie 5 in Science & Mathematics Mathematics

For your 411, My parents can't even understand it, and they agree that the book does not explain it well. If your not going to help, then don't bother answering this question...jeez.

2007-01-12 16:01:19 · update #1

8 answers

Apparently, they want you to factor this....

ax + bx = (a + b)x

a^2 + 2ab + b^2 = (a + b)^2

So, rewrite your problem as (a + b)x = (a + b)^2, which simplifies to x = a + b

2007-01-12 15:57:52 · answer #1 · answered by Anonymous · 0 0

It is very easy Maria
ax+bx=a^2+2ab+b^2
=> x(a+b)=(a+b)^2
=>x=(a+b)^2/(a+b)=a+b

2007-01-13 00:36:58 · answer #2 · answered by alpha 7 · 0 0

ax + bx = a^2 + 2ab +b^2
x(a+b)=(a+b)^2 divide both sides by a+b
x=a+b

2007-01-13 00:38:40 · answer #3 · answered by yupchagee 7 · 0 0

ax+bx=(a+b)x

so substract it from both sides

0 = -(a+b)x +(a+b)^2

0 = (a+b)((a+b)-x)

divide both sides by (a+b)

0 = (a+b-x) ---> x = a+b

check
a(a+b) +b(a+b)= a^2 +ab +ba +b^2 = a^2 +2ab +b^2

2007-01-13 00:03:53 · answer #4 · answered by Dr Dave P 7 · 0 0

as other people have noted"


/************************************************************/
x = a + b, with the condition

{ x not equal to 0 } <==== necessary condition
OR
"a" is not equal to "b".

There *was* a step
x (a + b) = (a + b)^2
followed by dividing both sides by (a + b) ...
however, this is valid ONLY when (a + b) not = 0
/************************************************************/


This might sound "picky", but

{x = 0} leads to a contradiction which means it is NOT a solution.

{ x = 0 } =>
{ (a + b)=0 }

but if (a + b)=0 then x = 12 satisfies the equation ...

which contradicts the original statement "x = 0"

when contradictions occur, something's wrong;

to avoid contradictions, it MUST be the case that x not equal 0.

which implies that "a" is not equal to "b".

2007-01-13 00:32:32 · answer #5 · answered by atheistforthebirthofjesus 6 · 0 0

~first, substitute n's for the a's, q's for the x's, y's for the b's and check you book again. You may just be making a spelling error. If that doesn't work, talk to your teacher. That's what they get paid for. Since the book can't help because you are too lazy to spend the time to learn the material, or to learn how to learn the material, maybe you should just drop the course.

2007-01-12 23:59:23 · answer #6 · answered by Oscar Himpflewitz 7 · 0 2

I assume the question is to solve for x... Factor both sides!
(a+b)x = (a+b)²

Divide by the common factor (a+b)...
x = a+b.

2007-01-12 23:58:21 · answer #7 · answered by Anonymous · 0 0

Factor to arrive at
x(a+b)=(a+b)(a+b)
Hmmm....
x=(a+b)

2007-01-13 01:00:18 · answer #8 · answered by Anonymous · 0 0

fedest.com, questions and answers